Evaluation of risk factors for intrauterine foetal death during third trimester of pregnancy: a hospital-based cross-sectional study - Bhasme, Manjushree; Moray, Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: In most cases of intrauterine foetal death (IUFD) in which the aetiology is known, a recurrence risk can be determined, and sometimes prenatal diagnosis and prevention are possible. In the present study, we evaluated the risk factors for intrauterine foetal death during 3rd trimester of pregnancy. Methods: This was a hospital based cross sectional study, which was conducted in department of obstetrics and gynecology in tertiary Government Teaching Hospital in North Maharashtra for the period of 24 months. We enrolled 131 patients attending ANC OPD/labour room in their 3rd trimester of pregnancy who were diagnosed to have IUFD. Results: There were 131 stillbirths out of 6402 live births hence incidence of IUFD was 20 per 1000 birth. IUFD was maximum seen in age group of 21 to 35 years (83.2%). Mortality was higher in un-booked cases (81.7%) and maximum (83.2%) mothers were from rural area. Most common presenting complaint was pain in abdomen (29.8%) followed by bleeding per vaginum in 16.8%. Only a small percentage i.e. 6.9% had no complaint. Hypertensive disorder of pregnancy (preeclampsia, eclampsia, chronic hypertension) was found to be an important comorbid factor among patients of IUFD which accounts for 31%. About 54.2% stillborn were males showing male preponderance. Post partum complications were relatively rare but most frequent was occurrence of severe anaemia due to APH. Maternal mortality occurred in 0.8% cases. Conclusions: In conclusion, IUFD is closely associated with maternal health disorders and demo-socioeconomic factors are highlighting the need for improved antenatal care and management to mitigate risks.